Analysis of patients' attitudes towards medical service prices in different regions based on grey relational theory. Issue 2 (1st April 2019) - Zhang, Chongxu; Duan, Lizhong; Liu, Hangyu; Zhang, Yinran; Yin, Lili; Sun, Qiaoqiao; Lu, Qi
Abstract : Purpose: The purpose of this paper is to understand the attitude of patients towards the current medical service price and the effect of policy implementation, and explore the existing problems of the current medical service price policy in the region in order to provide a research basis for the dynamic adjustment mechanism of the medical service price. Design/methodology/approach: Literature analysis and expert interviews are used to design the questionnaire of the dynamic adjustment of medical service price formation mechanism. A convenient sampling method is used to extract data of 600 patients from the five areas, namely Beijing, Tianjin, Hebei, Shandong and Liaoning, on-site to fill out the paper-based questionnaire and electronic questionnaire. The grey relational analysis is used to explore the difference in the attitudes of patients towards the price of the medical service. Combined with the research results and expert interview results, some improvement suggestions related to the current price policy of medical service in five areas are put forward. Findings: The overall average score of respondents in the five areas, namely Beijing, Tianjin, Hebei, Shandong and Liaoning, is found to be 3.861. In terms of surgical operation fee and examination fee, the average score is higher than 4, i.e. 4.097 and 4.011, respectively, indicating "relatively high" nodes. According to grey relevancy sorting, the correlation between the health service price attitude and the overall score in the five regions is in the following order: Shandong > Tianjin > Beijing > Liaoning > Hebei. Originality/value: In this study, patients' attitude towards the current price of medical services in their local areas, Beijing, Tianjin, Hebei, Shandong and Liaoning, is investigated in order to explore the existing problems of medical service price reform and thus provide the basis for further improvement in the medical service price policy.